Development of a Productive Waqf Management Model as an Alternative Source of Income for Islamic Higher Education - Isnaeni, Ahmad; Pratomo, Dimas; Farhana (Universitas Islam Negeri Raden Intan Lampung, 2026)
Developing a productive waqf management model as an alternative source of income is a strategic need for Islamic higher education in Indonesia, especially amidst the increasing need for sustainable financing. However, waqf management in educational institutions still faces various problems, such as low literacy in productive waqf, suboptimal asset utilization, limited human resources, and weak public trust due to transparency and accountability issues. This study aims to analyze the management of productive waqf and formulate a development model in Islamic higher education. The study used a qualitative evaluative approach through field studies at the Waqf Board of Pondok Modern Darussalam Gontor and STF UIN Jakarta. Data were collected through observation, interviews, and questionnaires, then analyzed using data triangulation, SWOT, IFAS, and EFAS. The results indicate that both institutions are in Quadrant I, making an aggressive growth strategy a relevant approach. The novelty of this study lies in the productive waqf management model that integrates waqf literacy, professionalization of governance, asset optimization, institutional collaboration, and continuous evaluation as the basis for the financial independence of Islamic higher education. This model can be adapted by Islamic universities according to their institutional character, asset potential, social networks, and management capacity in a contextual and sustainable manner.